Instructions to Authors ”“ Guidelines for Publication (Sustainability in Debate, 2012)
The journal Sustainability in Debate (SeD), interdisciplinary in its scope, publishes original texts about the several dimensions of sustainability. It goal is to create a direct channel for debates about sustainable development, environmental management, socioenvironmental conflicts, the state of the environment, environmental governance, among other matters.